2017
DOI: 10.1097/acm.0000000000001476
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Student Empathetic Engagement, History-Taking, and Communication Skills During Electronic Medical Record Use in Patient Care

Abstract: The findings suggest that a simple intervention providing specialized training in EMR-specific communication can improve medical students' empathic engagement in patient care, history-taking skills, and communication skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…2 shows a remarkable increase in the number of studies available per year since 1980, with a striking increase of 122% between periods 2000–2009 and 2010–2017. Most studies were featured in the Americas (n = 25) [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ], followed closely by Europe (n = 24) [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ]. Specifically, the majority were carried out in the United States (US) (n = 23) [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 shows a remarkable increase in the number of studies available per year since 1980, with a striking increase of 122% between periods 2000–2009 and 2010–2017. Most studies were featured in the Americas (n = 25) [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ], followed closely by Europe (n = 24) [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ]. Specifically, the majority were carried out in the United States (US) (n = 23) [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , …”
Section: Resultsmentioning
confidence: 99%
“…Variability was observed in the disclosure of further participant demographic information, specifically concerning first language, gender and mean age. Only 24 papers specified whether students had previous experience in NTS learning [ 26 , 28 , 32 , 35 , 39 , 41 , 44 , 45 , 52 , 55 , 61 , 63 , 64 , [67] , [68] , [69] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important that students know how to communicate effectively within the EPR and know when to adjust their modality of communication according to the situation [36]. Training related to EPR communication has also been shown to improve history taking skills and empathetic engagement in patient care [37].…”
Section: Discussionmentioning
confidence: 99%
“…We surmise that this incongruity in documentation could reflect that palliative care consult teams may be beneficial in clarifying these crucial aspects of care, which is reflected in the EMR, therefore improving the informed consent process of inpatients with life-limiting illness on various forms of life support. A recent study in Academic Medicine demonstrated that medical student training in EMR-specific communication improved “empathetic engagement…and communication skills.” 16 This intimates that additional training in utilization of the EMR as a communication tool could be advantageous for highlighting patient preferences and interteam communication.…”
Section: Discussionmentioning
confidence: 97%